2022
DOI: 10.3390/biology11121744
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Nutrition Drive the Gut Microbiota Succession and Host-Transcriptome Interactions through the Gilthead Sea Bream (Sparus aurata) Production Cycle

Abstract: Fish genetically selected for growth (GS) and reference (REF) fish were fed with CTRL (15% FM, 5–7% FO) or FUTURE (7.5% FM, 10% poultry meal, 2.2% poultry oil + 2.5% DHA-algae oil) diets during a 12-months production cycle. Samples from initial (t0; November 2019), intermediate (t1; July 2020) and final (t2; November 2020) sampling points were used for Illumina 16S rRNA gene amplicon sequencing of the adherent microbiota of anterior intestine (AI). Samples from the same individuals (t1) were also used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 123 publications
(146 reference statements)
1
12
0
Order By: Relevance
“…Microbiota research is a fast-growing field in aquaculture with important implications for fish nutrition, health, and welfare (Brugman et al, 2018). In particular, gilthead sea bream (Sparus aurata) is one of the main cultured fish in the Mediterranean (APROMAR, 2020), and recently, many studies have been conducted to unravel its intestinal microbial dynamics (Naya-Català et al, 2021a, 2022bPiazzon et al, 2020;Solé-Jiménez et al, 2021), as the gut microbiome plays a key role in maintaining the health status in fish, including the immune system response and digestion functions (Reda et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota research is a fast-growing field in aquaculture with important implications for fish nutrition, health, and welfare (Brugman et al, 2018). In particular, gilthead sea bream (Sparus aurata) is one of the main cultured fish in the Mediterranean (APROMAR, 2020), and recently, many studies have been conducted to unravel its intestinal microbial dynamics (Naya-Català et al, 2021a, 2022bPiazzon et al, 2020;Solé-Jiménez et al, 2021), as the gut microbiome plays a key role in maintaining the health status in fish, including the immune system response and digestion functions (Reda et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their presence after the IMT may be associated to either environmental factors or to factors intrinsic to the fish species such as their physiology, or genetic background, as both bacterial genera have been previously reported as part of the autochthonous fish microbiota 72 – 74 . Neither of these genera were maintained in the long-term (36 days post-IMT), though it may be due to the higher impact of the GSB diet, as the abundance of Brevinema in the fish gut mucosa has been shown to be easily modulated by the ingredient composition of the diet 75 , 76 , or due to competition with other bacteria after the IMT. Indeed, the competition among bacterial populations and their subsequent decrease in abundance of some may free up gut niches and resources needed for the emergence and growth of novel bacterial species, such as those belonging to the genera Acinetobacter and Corynebacterium , which were not present in the gut microbiota of Atlantic salmon or gilthead seabream from the pre-IMT group, nor in the GSB diet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the decrease in Vibrio and increase in Escherichia-Shigella were maintained in all sampling times post-IMT, with the latter showing an increasing colonization of gilthead seabream gut over time. Escherichia-Shigella is habitually found in the intestine of farmed gilthead seabream 75 , 84 , and have been reported as part of the core gut microbiota in some fish species 85 – 87 ; thus, its constant increasing abundance may be attributed to its survival and persistent growth over time as part of the gilthead seabream core microbiota. The persistency of the core microbiota may be consistent with the high abundance of the ASVs which were shared among gilthead seabream fed the GSB and the salmon diets and the group not submitted to the IMT (post-AMs) at both 7 and 16 days post-IMT, as shown in the Venn diagram (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the complex relationships between the physical and biological components of aquaculture systems in the context of climate change and human population growth are one of the key future challenges in animal food production [ 3 , 4 ]. Current research on gilthead sea bream ( S. aurata ), a highly cultured species in the Mediterranean, indicated that the gut microbiota is a reliable criterion to evaluate the success of selective breeding with changes in diet composition [ 5 , 6 , 7 ]. However, our understanding about these kinds of dynamics is at an infancy state, due to their inherent complexity, the multiple biotic and abiotic factors involved, and the enormous variability of mucosal microbial populations among distinct individuals of the same population [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%